2022
DOI: 10.1093/emph/eoac010
|View full text |Cite
|
Sign up to set email alerts
|

Mutation rate of SARS-CoV-2 and emergence of mutators during experimental evolution

Abstract: Background and objectives To understand how organisms evolve, it is fundamental to study how mutations emerge and establish. Here, we estimated the rate of mutation accumulation of SARS-CoV-2 in vitro and investigated the repeatability of its evolution when facing a new cell type but no immune or drug pressures. Methodology We performed experimental evolution with two strains of SARS-CoV-2, one carrying the originally describ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
100
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 50 publications
14
100
0
1
Order By: Relevance
“…Global epistasis of this nature can exist along side epistasis of specific amino acid changes as for example suggested for the S:N501Y mutation (Martin et al, 2021). Differences in diversification of SARS-CoV-2 with and without the S:D614G mutation where also observed in evolution experiments by Amicone et al (2022), who concluded that these differences were not due to a change in base line mutation rate but had selective origin.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Global epistasis of this nature can exist along side epistasis of specific amino acid changes as for example suggested for the S:N501Y mutation (Martin et al, 2021). Differences in diversification of SARS-CoV-2 with and without the S:D614G mutation where also observed in evolution experiments by Amicone et al (2022), who concluded that these differences were not due to a change in base line mutation rate but had selective origin.…”
Section: Discussionmentioning
confidence: 85%
“…An evolutionary rate of 6 synonymous changes per year at around 9700 positions corresponds to a per-site evolutionary rate of 6.2 × 10 −4 /site/year or 1.7 × 10 −6 /day, slightly higher than the estimated base-line mutation rate of 1.3 × 10 −6 /day (Amicone et al ., 2022). The total evolutionary rate within variants after mid 2020 (starting with 20E) is in the range of 9-16 changes per year, corresponding to a per site rate of 3 − 5 × 10 −4 /site/year, consistent with recent estimates by Hill et al .…”
Section: Discussionmentioning
confidence: 95%
“…Should booster doses not be available or not be accepted particularly as more infectious and potentially more severe subvariants emerge, hospital admissions may once again overwhelm health systems. This compounded with the potential for double epidemics with influenza and respiratory syncytial virus (as has been reported in Australia [ 15 ]) escalates the need for stronger preparedness for such eventualities given the high mutation rate of SARS-CoV-2 [ 16 ]. Therefore, it is prudent for countries to continue targeting and supporting vaccination boosting campaigns for all.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Recent research showed that the rate of spontaneous mutation in SARS-CoV-2 is 1.3 × 10 –6 ± 0.2 × 10 –6 per base per infection cycle. 11 The repeatedly mutating residues can alter the transmissibility (viral spread) and virulence (viral ability to enter and replicate inside host cell) of SARS-CoV-2 and decrease the efficacy of vaccines/drugs, thus posing serious challenges to the discovery of drugs against multivariant strains of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%